2004
DOI: 10.1021/cm035323j
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and Separation Characteristics of Polypeptide-Functionalized Polycarbonate Track-Etched Membranes

Abstract: The use of polypeptide-functionalized membranes with known porosity and uniform pore sizes allows a better understanding of the separation characteristics in nanodomains. A stimuli-responsive polypeptide, poly-L-glutamic acid (PLGA), was immobilized on a polycarbonate track-etched (PCTE) membrane. First, PCTE membrane was gold-coated under convective conditions, and a thiol, 3-mercapto 1,2-propanediol (MPD), was chemisorbed on the modified surface. Second, the MPD molecule was oxidized with sodium periodate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
0
38
1
Order By: Relevance
“…Alternatively, steric selectivity has been achieved by modifying the nanopore surfaces with polymer molecules that respond to environmental stimuli. [8] For instance, the water permeation rate through track-etched nanopores produced in polymeric films has been controlled by grafted macromolecules that respond to changes in environmental conditions, including pH, [9,10] light, [11] and ion concentration. [12] A number of polymer-based stimuli-responsive membranes have been recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, steric selectivity has been achieved by modifying the nanopore surfaces with polymer molecules that respond to environmental stimuli. [8] For instance, the water permeation rate through track-etched nanopores produced in polymeric films has been controlled by grafted macromolecules that respond to changes in environmental conditions, including pH, [9,10] light, [11] and ion concentration. [12] A number of polymer-based stimuli-responsive membranes have been recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two, the membrane-based reverse osmosis (RO) processes have made significant strides during the last three decades and are being widely used around the world [3][4][5][6][7][8][9][10]. However, the cost-effectiveness of RO processes is adversely affected by Understandably, current research emphasis is directed toward improving the membrane material for robustness and higher permeate flux [8,10,[11][12][13][14][15][16]. Concurrently, significant progresses have been made toward the development of forward osmosis (FO) and membrane distillation processes [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Smuleac and coworkers [195] demonstrated that the MWCO of Na 2 SO 4 salt was higher in the membranes with lower pore sizes (a difference up to 800% for a feed concentration of 2 mM).…”
mentioning
confidence: 99%
“…Other nanoporous polymeric systems such as polyimide [193], polyethylene [194], or polycarbonate (PC) [195] have also been investigated. Smuleac and coworkers [195] demonstrated that the MWCO of Na 2 SO 4 salt was higher in the membranes with lower pore sizes (a difference up to 800% for a feed concentration of 2 mM).…”
mentioning
confidence: 99%
See 1 more Smart Citation